The patterns of trophic transfer of microplastic ingestion by fish in the artificial reef area and adjacent waters of Haizhou Bay. (April 2022) - Zhang, Shuo; Wang, Nuo; Gong, Siming; Gao, Shike
Abstract: Plastic pollution has become a threat to the global marine environment. Many studies have shown that marine organisms are at risk of plastic ingestion, but there is still a lack of relevant research in the artificial reef area and adjacent waters of Haizhou Bay, located in the western Yellow Sea. The study of MPs will provide useful information for MPs pollution in the artificial reef food webs, as well as the understanding of MPs trophic transfer by reef fish. In this study, we quantified plastic ingestion by marine fish in artificial reef areas and adjacent waters (Natural area, NA; Aquaculture area, AA; Estuary area, EA; Artificial reefs area, AR and Comprehensive effective area, CEA) and analysed the related possible influencing factors. Of the 146 fish samples examined, 100% of fish ingested plastics, and 98.9% of these particles were microplastics (MPs) (<5 mm), with 3.00 ± 2.63 pieces/fish. The main types and colours of MPs were fibre (95.9%) and blue (84%). The MP quantity of AR and AA were significantly higher than that of CEA ( P  < 0.05) and there is no significant difference among other habitats. The MP ingestion by pelagic fishes was significantly lower than that of demersal fishes ( P  < 0.05). MP ingestion by omnivores was significantly higher than that by carnivores and planktivores ( P  < 0.05). The body length (body weight) of four species ( Larimichthys polyactis : 17.7–16.7 cm (16.01–59.41 g); Collichthys lucidus : 8.1–14.3 cm (19.65–56.92 g); Tridentiger barbatus : 5.9–9.2 cm (3.37–19.1 g); Cynoglossus joyneri : 10.1–18.7 cm (5–45 g)) had no significant correlation with MP ingestion ( P  > 0.05). Our results showed that MPs in this region are ubiquitous (i.e., the MP ingestion rate was as high as 100%). We infer that there is a transfer mechanism in MPs from pelagic to benthic fish in this area, and there is weak biomagnification with the trophic transfer of the food chain (TMF = 1.62). However, more practical studies still need to verify whether MPs are actually transferred to humans through trophic transfer from the marine food web. Highlights: The determination of characteristics of MPs ingested by fish in different habitats The variation in MPs in fish with different feeding habits and feeding strategies The relationship between biomagnification, body length, and MP ingestion by fish